The Good Serials Department, 1st edition - Gellatly, Peter (Routledge, 2020)
This book, first published in 1990, examines in detail 12 serials departments, both large and small, that experts have selected as representative examples of notable serials departments. The departments have in common a general reputation in the serials field as being good operations, in the sense of providing optimum services to their users despite the challenges of current-day problems in financial planning and collection re-evaluation and shaping. The examples offered serve mainly to suggest what works well in the serials operation today. Despite the lack of space devoted to the good serials department or the often crisis-oriented approach to serials problems that is occasionally emphasized in the literature, the ‘good serials operation’ undeniably exists and always has. Certain serials departments receive the utmost praise from librarian colleagues and faculty/student users alike. This authoritative volume shows that good serials librarianship remains what it has always been - a means of providing serials and the information in them to an ever-widening audience of readers and researchers. Economic changes may alter the pattern of serials department services, but they do not alter the real and ultimate goals of the serials department.